Risk Behavior of Tiom Community Related with Helminthiasis at Lanny Jaya District, Papua Province, Indonesia - Gurendro Putro (Journal of Global Pharma Technology, 2020)
Background: Helminthiasis is an infectious disease which is one of the severe health problems in Indonesia. The worm can reduce intelligence, inhibit the growth of children, and even cause death. The behavior of a clean and healthy life is expected to be able to encourage the community to improve the quality of daily health behaviors to cope with helminthiasis. Objective: to assess risk factors in healthy hygiene behaviors that has the potential to cause helminthiasis. Method: A descriptive retrospective research. The material is interviews form and library data assessment. Data collection is done by listening, direct recording, recording audio, and video provided. Data retrieval is done by the time-limited sampling method. The data obtained were processed and analyzed descriptively. Results: It was found that the community consisted of local communities and migrants. The risk factors for clean and healthy living that have the potential to cause helminthiasis are divided into two, namely: (1) Hygiene and living environment sanitation (2) Personal hygiene and sanitation which includes; the habit of washing hands is still low, not wearing footwear, the practice of cutting nails that are still weak, open defecation habits, bathing habits that are very rarely done, drinking water and eating raw food (3) Risk of eating pork at a "barapen" stone grilling ceremony. Conclusion: Risk factors in healthy hygiene behavior that have the potential to cause helminthiasis are health sanitation of residential, inadequate personal hygiene, and cooking pork at a "barapen" stone grilling ceremony, which is considered insufficient to kill worms. Keywords: Clean and healthy lifestyle, Helminthiasis, Tiom, “Barapen” Ceremony, Tiom, Papua Indonesia.